Mawlâna Jalâleddîn-I Rûmî the life, work and the Mawlawî order - Kayadibi, Saim; Safak, Yakup (Olgun Çelik Printing House, 2007)

(untitled)
This book briefly explores the life, work and the Mawlawi order of Mawlâna Jalâleddín Rûmî who was born in 30 September 1207 in Balkh, where is located at the present northern Afgani-stan. This city was, at that time, one of the main central city of Khorasan region. His original name is Mohammed. The name of “Mawlâna” means “Our Mater or Excellency” was used as an esteemed title for great people and scholars. As to “Rûmî”, it was used for those who are from Anatolia. Mawlâna be-longed to a noble and a distinguished family. His mother was Mu’mine Khatun and his father was Bahaeddin Walad which was well known as the Sultan of Scholars (Sultan’ül-‘Ulama’). His elder brother Alâaddin Mohammed and sister was Fâtıma Khatun.